Functional characterization of sesquiterpene synthase from Polygonum minus - Ee, Su Fang; Mohamed Hussein, Zeti Azura; Othman, Roohaida; Shaharuddin, Noor Azmi; Ismail, Ismanizan; Zainal, Zamri (Hindawi Publishing Corporation, 2014)
Polygonum minus is an aromatic plant, which contains high abundance of terpenoids, especially the sesquiterpenes C15H24. Sesquiterpenes were believed to contribute to the many useful biological properties in plants. This study aimed to functionally characterize a full length sesquiterpene synthase gene from P. minus. P. minus sesquiterpene synthase (PmSTS) has a complete open reading frame (ORF) of 1689 base pairs encoding a 562 amino acid protein. Similar to other sesquiterpene synthases, PmSTS has two large domains: the N-terminal domain and the C-terminal metal-binding domain. It also consists of three conserved motifs: the DDXXD, NSE/DTE, and RXR. A three-dimensional protein model for PmSTS built clearly distinguished the two main domains, where conserved motifs were highlighted. We also constructed a phylogenetic tree, which showed that PmSTS belongs to the angiosperm sesquiterpene synthase subfamily Tps-a. To examine the function of PmSTS, we expressed this gene in Arabidopsis thaliana. Two transgenic lines, designated as OE3 and OE7, were further characterized, both molecularly and functionally. The transgenic plants demonstrated smaller basal rosette leaves, shorter and fewer flowering stems, and fewer seeds compared to wild type plants. Gas chromatography-mass spectrometry analysis of the transgenic plants showed that PmSTS was responsible for the production of β-sesquiphellandrene.